Bentuk Penyajian Beksan Lawung Ringgit Keraton Yogyakarta pada Acara Pembukaan Simposium Internasional Busana dan Peradaban Keraton Yogyakarta Tahun 2020 - Hendy Hardiawan; Agustinus Welly Hendratmoko (Journal of Mandalika Social Science, 2025)
Beksan Lawung Ringgit is one of the dances of the Yogyakarta Palace, created by Sri Sultan Hamengku Buwono I and subsequently reconstructed during the reign of Sri Sultan Hamengku Buwono X. The reconstruction of this dance was based on an ancient manuscript containing limited information; therefore, textual and contextual interpretation was required by adopting an existing choreographic structure and compositional framework. Beksan Lawung Ringgit, which was performed at the opening ceremony of the International Symposium on the Attire and Civilization of the Yogyakarta Palace in 2020, was the second occasion on which the dance was presented for public viewing. Overall, Beksan Lawung Ringgit is performed by six male dancers, each portraying a different character. The presence of characterization in this dance represents a unique and uncommon feature, particularly within the compositional conventions of the Lawung dance tradition. This study employs a textual approach to analyze the form of presentation and the various compositional aspects of Beksan Lawung Ringgit.